Pengaruh Media Sosial: Pinterest, Tiktok, Dan Instagram Terhadap Kreativitas Mahasiswa Fakultas Arsitektur Desain UPN Veteran Jawa Timur - Revinindia Oktaimanuella; Rizki Amelia Putri; Nashwa Aqila Yudhiestira; Vinsi Mareta Putri Jauzza; Fatih Parama Aji; Eni Nurhayati (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This research aims to investigate the influence of social media, such as Pinterest, TikTok, and Instagram, on the creativity of students at the Faculty of Architecture and Design at UPN Veteran East Java. The research method used is a quantitative approach by distributing questionnaires to a sample of students who are members of the Faculty of Architecture and Design. The results of this research show the significant influence of social media on student creativity in the context of architecture and design. Apart from that, this research also identified differences in the influence of different social media platforms on aspects of student creativity. It is hoped that these results will provide further insight into how social media influences the creative thinking patterns of architecture and design students. In conclusion, this research contributes to the understanding of the impact of social media on creativity among architecture and design students. The implications of this research can be used as a basis for developing a more effective approach to utilizing social media positively to increase creativity and quality of work in the future.